ANTROPOLOGI ISLAM DI INDONESIA - Muhamad Taufik Hidayat (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article studies the importance of religion understanding whichis reflected in their culture. The main position of people in Islam indicatesthat we have to understand Allah. Anthropologists learn the culture andsociety to understand the meaning and the core of religion and its role inman’s life. The cultural concept is basically a tool to see, to learn and tounderstand the religion which in its society.